INTEGRASI NILAI-NILAI TRADISIONAL DAN MANAJEMEN MODERN DALAM TRANSFORMASI KELEMBAGAAN PESANTREN: STUDI MULTI-KASUS PADA PESANTREN UNGGULAN DI INDONESIA - Asyhari, Muhamad Sidiq; Budianto, Kukuh (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research explores the integration of pesantren’s traditional values into contemporary management frameworks during the institutional transformation of prominent Islamic boarding schools in Indonesia. The study is grounded in the pressing necessity for pesantren to adapt to the dynamics of educational modernization while safeguarding their cultural and spiritual heritage. Adopting a qualitative methodology with a multiple-case study design, the investigation focused on three pesantren that have undergone notable reform yet preserved their core traditions. Data were obtained through comprehensive interviews, participatory observation, and analysis of institutional records, followed by interpretation using Miles and Huberman’s interactive model. The analysis indicates that transformation unfolds through three interconnected stages: embedding of vision and values, restructuring of managerial systems, and the development of tradition-oriented educational innovations. Transformational leadership, particularly that of the kiai, plays a pivotal role in facilitating reform while sustaining cultural legitimacy. Key values khidmah, ta’dzim, barakah, and ukhuwah are incorporated into managerial practices via symbolic, inclusive, and context-sensitive strategies. The study proposes a conceptual framework for pesantren transformation that merges value-based principles with modern management, offering a practical reference for advancing Islamic educational management in Indonesia. Ultimately, the findings suggest that effective institutional transformation is achievable when anchored in a robust spiritual vision, visionary leadership, and adaptive strategies grounded in local wisdom.